Comparison of the parameters of thermal comfort in a house built with green bricks with a conventional construction - Esteves, A. O. [UNESP]; Souza, T. M. [UNESP] (My University, 2015)
This project consists of the comparison of thermal comfort between a house made of green bricks and a construction made of conventional bricks. The green bricks are made of cement, water and soil and provide many benefits such as: material savings, reduced construction time, is easy to produce and can be done at the construction place and don’t consume fuel in the manufacture. At the structure of this bricks, have holes provides thermal and acoustic insulation, doesn’t allow the accumulation of moisture on the walls, facilitates the electrical and plumbing systems and promote the engagement of bricks, giving greater symmetry. It is intended to show and prove that this type of brick provides benefits for buildings. This project used the devices: thermometers with and without contact, anemometer, hygrometer and density meter solar power. With these equipaments are measured internal and external temperatures to buildings and bricks, wind speed, humidity and solar radiation intensity. The two buildings analyzed are located in the UNESP campus Guaratinguetá-Brazil. The results was positives, the green bricks provided the benefits mentioned above, showing that this type of construction can benefit society and the environment, encouraging their use.
Keywords: Ecological bricks; Energy efficiency; Green house; Thermal comfort